Deformation analysis in post-hospitalised patients with moderate SARS-CoV-2 infection. (4th February 2022) - Valatsou, A; Tsartsalis, D; Dimitroglou, Y; Tolis, E; Banos, A; Sfendouraki, E; Fragoulis, C; Patsourakos, D; Koukos, M; Kalompatsou, A; Chrysochoou, C; Pirounaki, M; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: SARS-CoV-2 infection is associated with multiple cardiac manifestations (1, 2). Global longitudinal strain (GLS) by speckle tracking echocardiography (STE) is a novel transthoracic echocardiography (TTE) measure of myocardial deformation, which could early recognize subclinical cardiac injury in COVID-19 patients (3, 4). Purpose: We aimed to explore GLS profiles in post-hospitalized COVID-19 patients to identify features of eventual subclinical cardiac injury and to investigate the possible correlation with the severity of infection. Methods: We enrolled 33 patients (mean age 59.2 ± 13, 64% men) with positive SARS-CoV-2 RT-PCR, hospitalized for moderate COVID-19 disease, with no admission to intensive care unit. Patients were submitted to TTE 1-2 months after discharge.  Images were anonymised and analysed offline by two accredited cardiologists. Clinical parameters and laboratory findings from hospitalization were also collected.  Acute myocardial infarction and pulmonary embolism were exclusion criteria. Results: Mean duration of hospitalization was 12.9 ± 8.0 days. Study population had normal systolic function with a mean LV ejection fraction 58.6% (±3.6) while the majority of patients had relative low values of LV global longitudinal strain, mean 15.2% (±2.3). Arterial hypertension was present in 51.5% of patients and a history of previous myocardial infarction was referred in 6.1% of the population. Only 24.2% of patients had elevated troponin levels during the previous in-hospital period (mean maximal value of hs-troponin  was 18.1 ±16.6 pg/mL) whereas  81.8% had abnormal D-Dimers values (mean 2424 μg /L, range ±2825) and 93.1% had high hs-CRP values (138.2 ±92.0 mg/L) . Duration of hospitalization had strong significant correlation with D-Dimers (rho: 0.708, p: <0.001) and hs CRP (rho:0383, p:0.028) and  marginal association with troponin ( rho: 0.335, p:0.056). Moreover, global longitudinal strain showed significant association with duration of hospitalization (rho:-0.545, p: 0.007). Traditional systolic indices as LVEF and the various diastolic parameters  showed no significant association with severity of disease reflected by the duration of hospitalization and the other clinical and laboratory biomarkers. Conclusion: Cardiac manifestations of SARS-CoV-2 infections could be present in mild to moderate disease and seems to associate with the severity of infection. The novel echocardiographic parameters such as GLS could add valuable information and identify  possible subclinical cardiac injury often unrecognized by traditional TTE examination.